"The Silenced Generation": The Communication Experiences of HIV-Positive Adolescents in Kenya. Issue 2 (3rd April 2019) - Otieno, Jescah; Obuya, Jared
ABSTRACT: HIV remains a major challenge in many contexts globally, and particularly in Kenya due to the high rates of infections among the youth. One of the challenges facing HIV management is the difficulty of communicating about it, especially among adolescents who face stigma associated with the disease. This phenomenological study examines the communication experiences of adolescents living with HIV/AIDS and their perceptions of these experiences. Data were generated through interviews with six HIV-positive adolescents, two caregivers, one social worker and one doctor, who were all selected purposively. The data were analysed thematically and presented in agreement with the themes. Relevant ethical considerations including confidentiality, protection from harm and informed consent were made. The overall perspective of HIV-positive adolescents is that adults accord them a limited platform to communicate their feelings and experiences. They are bombarded with messages of advice, commands, threats, and continuous lectures—a clear indication that the adults are not in touch with the reality of the life of an HIV-positive adolescent. Therefore, there is need for clear, well thought-out platforms for adolescents living with HIV to address their communicative needs.